An overview on marriage reconciliation process under the Law Reform (Marriage and Divorce) Act 1976 - Sowell, Sarafuddin Abdul Syahid; Abdul Hak, Nora; Mohd Zin, Najibah (2016)
The number of divorce cases in Malaysia has increased despite that the law provides reconciliation process to re-unite the couple in dispute. According to the statistic from National Registration Department of Malaysia, the divorce rate for both non-Muslim and Muslim couples as compared to the rate of marriage has steadily increased especially beginning the year 2001 (Siti Farhanan Md Sam & Puzziawati Ab Ghani, 2015). Malaysian laws provide avenues for disputing couples to reconcile their broken relationships. There have been criticisms by legal and social scholars on the current legal framework for reconciliation. The objective of this writing is to provide an overview of the current legal framework and process for marriage reconciliation in Malaysia and to identify issues and obstacles of the current legal framework for marriage reconciliation process. This research is based on the hypothesis that the current legal framework for marriage reconciliation has not been able to achieve the objective of preserving the marital relationship and improvements of the legal framework is required. This study will be based on analysing theory, concept, published data and literature relating to the law, the framework and the processes of the marriage reconciliation in Malaysia. The study will apply thorough analysis on the process of conducting the reconciliation session especially the methods applied during the reconciliation session.